Pengaruh Kinerja Keuangan Terhadap Dividen Payout Ratio dan Nilai Perusahaan - I Gusti Ayu Raka Heriyanthi (Jurnal Manajemen dan Bisnis, 2016)
of financial management functions. This research is aquantitative research that aims to determine the effect of the financial performance of thedividend payout ratio and company value. The population in this study are all manufacturedcompanies listed on the Stock Exchange. Research hypothesis testing technique used pathanalysis with AMOS software tool. The results showed that there was no financialperformance that affect enterprise value. In different circumstances, the results showed thatthe current ratio, debt equity ratio and total assets turn over effect on dividend payout ratio.Besides, the results also showed that there was no significant relationship between dividendpayout ratio with the enterprise value as well. The result confirmed the theory of ModiglianiMiller that stated dividend irrelevant. The results also confirmed the theory of signal. Thefinancial performance of the current ratio, debt equity ratio and total assets turnover canincrease or decrease the value of the dividend payout ratio.Keywords : Financial Performance , Dividend Payout Ratio and Value Companies